Higher probability of prodromal Parkinson disease is related to lower cognitive performance. (7th May 2019) - Bougea, Anastasia; Maraki, Maria I.; Yannakoulia, Mary; Stamelou, Maria; Xiromerisiou, Georgia; Kosmidis, Mary H.; Ntanasi, Eva; Dardiotis, Efthimios; Hadjigeorgiou, Georgios M.; Sakka, Paraskevi; Anastasiou, Costas A.; Stefanis, Leonidas; et al.
Abstract : Objective: Given the limited information on cognitive function before Parkinson disease (PD) clinical onset in the general population, we sought to assess prodromal PD (pPD) probability and relate it to detailed cognitive performance in a community cohort. Methods: In a population-based cohort of 1, 629 dementia-free and PD-free participants ≥65 years of age in Greece, we assessed probability of pPD according to the International Parkinson and Movement Disorder Society's criteria. Clinical cognitive diagnoses (cognitively unimpaired, mild cognitive impairment [MCI], dementia) considering neuropsychological testing and functional status were assigned in consensus conferences. Cognitive performance in 5 cognitive domains was assessed by a detailed neuropsychological battery and summarized in the form of z scores. We investigated associations between pPD probability (and its individual constituents) and cognitive outcomes. Results: The median probability of pPD was 1.81% (0.2%–96.7%). Participants with MCI had higher probability of pPD compared to those with normal cognition ( p < 0.001). Higher probability of pPD was related to lower performance in all cognitive domains (memory, language, executive, attention, and visuospatial function) ( p < 0.001). Lower cognitive performance was further associated with certain nonmotor markers of pPD, such as daytime somnolence, depression, urinary dysfunction, constipation, and subthreshold parkinsonism ( p < 0.001). Conclusions: Higher probability of pPD was associated with lower cognitive performance in all domains and higher probability of MCI. This may reflect a widespread pathologic process although future studies are warranted to infer causality. These results suggest to clinicians that they should assess cognition early, and to researchers that they should further look into the possible mechanisms that may underlie this observation.